Low‐power class‐AB 4th‐order low‐pass filter based on current conveyors with dynamic mismatch compensation of biasing errors. (7th February 2020) - Centurelli, Francesco; Monsurrò, Pietro; Stornelli, Vincenzo; Barile, Gianluca; Trifiletti, Alessandro
Summary: A 4 th ‐order Butterworth class‐AB current‐mode low‐pass filter is proposed, based on second‐generation Current Conveyors (CCII). Class‐AB operation allows high‐power efficiency and driving large loads with small quiescent currents. The CCII topology uses the class‐AB output buffer with error amplifiers: this topology is known to be sensitive to mismatch errors, which cause offsets in the error amplifiers, affecting the biasing current of the stage. This problem is solved via a control loop, which compensates the effect of mismatches. The technique is shown to be effective in Monte Carlo simulations with process variations and mismatches. Simulations have been carried out in 40 nm CMOS technology. The proposed filter achieves good power efficiency, thanks to the class‐AB architecture, and good dynamic range, thanks to the closed‐loop output buffer. A cut‐off frequency of 6 MHz, with 184 μW of total quiescent power consumption, is achieved, with a THD of ‐55 dB and a SNR of 49 dB. Abstract : A class‐AB current‐mode low‐pass filter is proposed, based on second‐generation Current Conveyors (CCII). The CCII topology uses the class‐AB output buffer with error amplifiers. This topology is known to be sensitive to mismatch errors: this problem is solved via a control loop, which compensates the effect of mismatches. The technique is shown to be effective in Monte Carlo simulations with process variations and mismatches. The proposed filter achieves very good power efficiency.